Job environment the Pancea on employee performance of selected Small and Medium Enterprises (SMEs) in the Kumasi Metropolis - Bonsu, Charles Akomea; Owusu, Edwin Eric; Appienti, Willian Ansah; Kwaku, Owusu Asabere (Technium Social Sciences Journal, 2022)
The study focused on the effect of job environment on employee performance of some selected SMEs within Kumasi Metropolis. Correlation as well as analytical survey research design were used. Respondents for this study were one hundred and twenty-nine (129) employees. This study employed two non-probability sampling techniques, namely convenience sampling, and purposive sampling techniques. This indicates that a low rewards system will have a slow increase in productivity. It is recommended that under the reward system, special commissions or allowances will be provided to staffs. The institution can also introduce the best staff of the month system based on perfect and more proactive staff and good delivery The study showed the offices have enough tools and equipment for working. Again, the study revealed that there is regular appraisal for promotion in the selected SMEs. The study recommended that; Management of the institutions should have safety-training programmes for its employees.